Inter-Ethnic Relations and Local Peace Campaigns: An Ethnographic Study in Abepantai Subdistrict, Jayapura City, Papua Province - La Mochtar Unu; Urip Wahyudin (Green Publisher Indonesia, 2026)
Multi-ethnic communities in Papua face vulnerability to horizontal conflict triggered by political polarization. Sustainable peace requires an understanding of local practices. This study aims to analyze inter-ethnic relations and the mechanisms of community-based peace campaigns in Abepantai Village, Jayapura City, Papua Province. This qualitative ethnographic research uses participant observation, in-depth interviews (n=27), and FGDs (n=3). Data are analyzed thematically following an interactive model. Inter-ethnic relations are symbiotic yet instrumental, based on economic exchanges such as between Buton farmers and Naffri landowners. Peace campaigns operate in two modes: (1) directly through conflict mediation by traditional/religious leaders, and (2) indirectly through cooperation in building houses of worship, holiday gatherings, and social gatherings that foster dialogue. This local cohesion is vulnerable to the influence of external identity politics narratives (OAP vs. non-OAP). Conclusion: Peace at the grassroots level results from socio-cultural practices and daily communication that are actively maintained. Its sustainability depends on the resilience of cross-ethnic social capital and the capacity of local institutions to negotiate external pressures.